1980
DOI: 10.1172/jci109855
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and Microtubules

Abstract: A B S T R A C T We examined the role of microtubules in platelet aggregation and secretion (release reaction) induced by the calcium ionophore A23187 (0. 8-5 ,uM). At these concentrations, platelet aggregation was preceded by a lag period of -1 min. Colchicine (an agent that disrupts microtubule assembly-disassembly) was shown to bind to platelet microtubules by employing [3H]colchicine at a concentration that is specific for microtubules in other tissues (10 nM). Colchicine prolonged the lag period, inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 23 publications
3
12
0
1
Order By: Relevance
“…This finding is consistent with a study by Karpatkin et al that demonstrated a decrease in platelet aggregation in response to ADP, epinephrine, and collagen when PRP was pre-incubated for 2 minutes with 250 μM to 2000 μM colchicine but not at lower concentrations [4]. Moreover, Bouaziz et al observed a decrease in microtubular content and tubulin polymerization when thrombin-stimulated platelets were pre-incubated for a longer time period (120 minutes) with 10 μM to 1000 μM colchicine, but demonstrated a modest 20% decrease in platelet aggregation only when these platelets were treated with 100 μM to 1000 μM colchicine [14].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is consistent with a study by Karpatkin et al that demonstrated a decrease in platelet aggregation in response to ADP, epinephrine, and collagen when PRP was pre-incubated for 2 minutes with 250 μM to 2000 μM colchicine but not at lower concentrations [4]. Moreover, Bouaziz et al observed a decrease in microtubular content and tubulin polymerization when thrombin-stimulated platelets were pre-incubated for a longer time period (120 minutes) with 10 μM to 1000 μM colchicine, but demonstrated a modest 20% decrease in platelet aggregation only when these platelets were treated with 100 μM to 1000 μM colchicine [14].…”
Section: Discussionsupporting
confidence: 92%
“…Mechanistic in vitro studies suggest that therapeutic concentrations of colchicine bind to platelet tubulin and modulate microtubular associated protease, which in turn either prevents phosphoprotein synthesis or degrades existing phospoproteins required for microtubular polymerization [4,15]. Based on our study, this putative mechanism of action may not translate into functional effects on platelet aggregation in the setting of therapeutic oral colchicine administration.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…29 47 At supratherapeutic concentrations, colchicine, through its microtubule effects, converts normal discoid platelets to rounded, irregular structures and inhibits platelet activation by decreasing calcium entry. 48 These mechanisms diminish in vitro platelet-to-platelet aggregation. In contrast, we demonstrated that standard clinical doses of colchicine do not decrease platelet-to-platelet aggregation but do diminish neutrophil-toplatelet aggregation, 49 suggesting that colchicine at physiological doses may provide an inhibitory role at the inflammation/ thrombosis interface without comprising homeostatic plateletto-platelet function.…”
Section: Colchicine and The Inflammation/thrombosis Interfacementioning
confidence: 99%